2011
DOI: 10.1002/dta.363
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo efficacy of PEGylated diisopropyl fluorophosphatase (DFPase)

Abstract: Highly toxic organophosphorus compounds that irreversibly inhibit the enzyme acetycholinesterase (AChE), including nerve agents like tabun, sarin, or soman, still pose a credible threat to civilian populations and military personnel. New therapeutics that can be used as a pretreatment or after poisoning with these compounds, complementing existing treatment schemes such as the use of atropine and AChE reactivating oximes, are currently the subject of intense research. A prominent role among potential candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…One of the ways for the mutant AChE to gain prolonged circulation time is a conjugation with polyethylene glycol. 16,37 Such an enzyme should retain all of the kinetic characteristics of its nonPEGylated form while having 20-fold greater mean residence time. 37 Further analysis of soman scavenging should also be directed to stereoselectivity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways for the mutant AChE to gain prolonged circulation time is a conjugation with polyethylene glycol. 16,37 Such an enzyme should retain all of the kinetic characteristics of its nonPEGylated form while having 20-fold greater mean residence time. 37 Further analysis of soman scavenging should also be directed to stereoselectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, in a preliminary in vivo study, Melzer et al . found that addition of pegylated DFPase minimizes lethality in rats challenged with a subcutaneous 3xLD 50 dose of soman, thereby highlighting its potential for in vivo use (Melzer et al, 2012).…”
Section: Enzymes For Decontaminationmentioning
confidence: 99%
“…DFPase also has a much more accessible active site than PON1, 19 lacking the three helices that decorate the top of the β-propeller in PON1 and help it interact with HDL, thus also sequestering the active site from solvent. 19 , 32 , 34 In addition, although DFPase is far less studied than PON1, there has nevertheless also been interest in developing engineered variants of this enzyme that can be used as a biotherapeutic, 45 and the enzyme has been the subject of several biochemical, structural and also more recently computational studies (e.g., refs ( 1 ), ( 36 ), ( 39 ), ( 44 ), and ( 46 48 )).…”
Section: Introductionmentioning
confidence: 99%